2020
DOI: 10.1117/1.oe.59.10.102413
|View full text |Cite
|
Sign up to set email alerts
|

Hardware implementations of computer-generated holography: a review

Abstract: Computer-generated holography (CGH) is a technique to generate holographic interference patterns. One of the major issues related to computer hologram generation is the massive computational power required. Hardware accelerators are used to accelerate this process. Previous publications targeting hardware platforms lack performance comparisons between different architectures and do not provide enough information for the evaluation of the suitability of recent hardware platforms for CGH algorithms. We aim to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…This scalability is important for HoloBlade to see significant uptake. Moreover, using a FPGA allows dedicated CGH hardware accelerators to be implemented directly in the FPGA fabric, supporting the current trends within the field [19]; performing the complex CGH routines in dedicated hardware increases performance and reduces the software complexity for researchers.…”
Section: Interfacing Logicmentioning
confidence: 82%
“…This scalability is important for HoloBlade to see significant uptake. Moreover, using a FPGA allows dedicated CGH hardware accelerators to be implemented directly in the FPGA fabric, supporting the current trends within the field [19]; performing the complex CGH routines in dedicated hardware increases performance and reduces the software complexity for researchers.…”
Section: Interfacing Logicmentioning
confidence: 82%
“…In traditional static holography, the amplitude and phase of the light reflecting from an object are recorded into a photosensitive material (e.g., dichromated gelatin) by interfering the object beam with the reference beam ( Fig . ) 6 . The photosensitive material with the recorded interference pattern is referred to as a hologram.…”
Section: Using Holographic Technologies To Create Compact Ar Hudsmentioning
confidence: 99%
“…4a). 6 The photosensitive material with the recorded interference pattern is referred to as a hologram. For reconstruction of the object beam, a coherent beam having the same wavelength as the reference beam is used to illuminate the hologram from the same direction as the recording reference beam.…”
Section: Using Holographic Technologies To Create Compact Ar Hudsmentioning
confidence: 99%
“…Northwestern Universitybased research performed in a full vehicle driving simulator demonstrated a 30 percent improvement in eyes-on-road time with the addition of surface haptics. 6 Designers also should seek to minimize the number of menus needed to access controls, as this contributes to cognitive load.…”
Section: Key Considerations For Automotive Hapticsmentioning
confidence: 99%